2006
DOI: 10.1152/ajpregu.00108.2006
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic basis for impaired muscle force production and neuromuscular compensation during sprint cycling

Abstract: For both different individuals and modes of locomotion, the external forces determining all-out sprinting performances fall predictably with effort duration from the burst maximums attained for 3 s to those that can be supported aerobically as trial durations extend to roughly 300 s. The common time course of this relationship suggests a metabolic basis for the decrements in the force applied to the environment. However, the mechanical and neuromuscular responses to impaired force production (i.e., muscle fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 60 publications
2
37
0
Order By: Relevance
“…8; see also Refs. 33 and 42) simplification that we have used conservatively here and previously (12,13,51). Nonetheless, the data indicate that the level of force production responsible for the transition from primarily aerobic metabolism to a net reliance on anaerobic sources of ATP resynthesis can differ markedly while completing the same muscular task.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…8; see also Refs. 33 and 42) simplification that we have used conservatively here and previously (12,13,51). Nonetheless, the data indicate that the level of force production responsible for the transition from primarily aerobic metabolism to a net reliance on anaerobic sources of ATP resynthesis can differ markedly while completing the same muscular task.…”
Section: Discussionmentioning
confidence: 81%
“…8). In contrast, in trials with levels of force production that exceeded those eliciting the aerobic peaks, we measured progressive increases in EMG activity, as others have (12,15,41). In these trials, which necessarily require a net reliance on anaerobic metabolism, the compensatory behavior began at the outset of each exhaustive trial and continued contraction-by-contraction until the point of failure (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore be that higher iEMG activity in the slower trials resulted from neuromuscular compensation for reduced force production capability in the skeletal muscles. Although the exact nature of any differences in peripheral physiological status at the beginning of the trials was unknown, this phenomenon has been demonstrated by Bundle et al, 30 who found compensatory neuromuscular activity resulted from increased reliance on anaerobic metabolism for force production. These authors also suggested that, regardless of specific physiological mechanisms, the principle of compensatory neuromuscular activity for impaired muscle contractile function seems likely to be a general response.…”
Section: Discussionmentioning
confidence: 96%
“…As superior performances were associated with a less conservative strategy, and RPE was similar throughout fastest and slowest trials then, in this study, it seems that affect may have been a more important regulator of pacing strategy than RPE. Rating of perceived exertion has previously been demonstrated to be influenced by acid-base status, 30,31 with lower pH being associated with higher RPE at a fixed workload. In the present study, and despite similar RPE values throughout exercise, postexercise pH was lower and blood lactate concentration was higher following fastest trials.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that the higher neuromuscular activity despite a lower power output in the slower trials was evidence for neuromuscular compensation for a sub-optimal peripheral physiological status. This concept of neuromuscular compensation had previously been described by Bundle et al (2006) who suggested that compensatory neuromuscular activity occurs in response to impaired muscle contractile function. Therefore, in the present study the finding of a higher EMG activity during the placebo trials may be explained by suggesting that due to a relatively inferior peripheral physiological status with regards to the demands of the exercise task, a greater degree of neuromuscular activity was required in order to produce the same absolute muscular work rate.…”
Section: Discussionmentioning
confidence: 90%